Synchronous Output Control System of Two Megawatt Hot Cathode Bucket Ion Sources for NBI - 赵远哲 吴德云 胡纯栋 张小丹 崔庆龙 张睿 林宇莲 盛鹏 (等离子体科学与技术：英文版, 2015)
Synchronous output of one beam line＇s two megawatt hot cathode bucket ion sources is required when Neutral Beam Injector （NBI） works on the Experimental Advanced Supercon- ducting Tokamak （EAST）. Neutral Beam Injector Control System （NBICS） realizes synchronous output and asynchronous output of two ion sources with network communication and hardware triggers. And the synchronous time can be set by operator. In synchronous mode, two megawatt hot cathode bucket ion sources can produce neutral beams at any relative time with higher energy than two sources＇ asynchronous output. Two megawatt hot cathode bucket ion sources＇ synchronous output makes an important contribution to NBI system of 4-8 MW with 10-100 s pulse length and provides more and better parameters for EAST physical experiments.